Edward V. Coughlin, La teoría de la sátira en el siglo XVIII. Juan de la Cuesta, Newark, 2002; 155 pp. - Cazés, Dann (El Colegio de México, 2003)
Se reseñó el libro: La teoría de la sátira en el siglo XVIII.